Interactive Technologies in Musical and Arts Education - Y. Y. Glazyrina (Russian State Vocational Pedagogical University, 2015)
The paper substantiates the introduction of interactive techniques in music and arts education, and analyzes the definitions of interactivity - a key term of the modern educational paradigm. Various interpretationsof interactivity and its components - interaction, communication, dia logue, polylogue, interpretation, reinterpretation, intonation, feelings, comprehension, generalization (reflection), and experience - are given. In the methodology context, the author traces out the similarity of interactive concepts in general didactics and the humanities knowledge (M. M. Bakhtin, V. S. Bibler), and maintains that the main components of interactive teaching include the basic categories of culture, art, music, and psychology of artistic perception and creativity. Therefore, similarity of the content and approach to interpreting the conceptual terminological apparatus of interactive education makes it possible to implement the interactive techniques in teaching the cycle of music and arts disciplines.